The Sati System in Nepal: Religious Conviction and Social Complications - Manandhar, Tina (Nepalese Culture, 2022)
The practice of widow burning ‘Sati Pratha’ was prevalent in Nepal from the ancient period up to its abolishment during the Rana regime by Prime Minister Chandra Shamsher. The practice was at its apex during the medieval period in Nepal when not only the widow but in some cases mother, slave girls, and even boys were immolated most probably against their wish. This was because most of the religious texts praised it and took it as one of the glorious acts one can perform to sanctify themselves and their lineage. Such religious conviction encouraged social complications and in some cases, such acts were performed to gain political advancements also. This paper tends to analyze the different factors which encouraged/forced innocent women to give up their life and how the cruel act of burning a person gained such popularity among the people. Along with its history to the actions taken in phase-wise for its abolishment in case of Nepal are discussed.